Human skin bacterial flora differ with altitudes in different ethnic groups of Nepal - Shrestha, Dipendra; Shrestha, Raju; Hendriksen, Rene S.; Sharma, Luna Bhatta; Bhatta, Dwij Raj (Asian Journal of Medical Sciences, 2019)
Background: Largest organ of human body, the skin, is colonized by millions of microorganisms, most of which are not only harmless but also beneficial to the host. Human skin microbes depend upon geographical variations, ethnicity and various host factors. Despite several studies on human skin microbiota in various parts of the globe, it has not been studied in Nepalese population. Aims and Objective: To identify skin bacterial normal flora in different ethnic groups residing in different altitude of Nepal. Materials and Methods: We cultured skin swabs of 166 randomly selected volunteers belonging to 10 major ethnic groups from 3 distinct geographical altitudes of Nepal, viz. Bharatpur (415 m from sea level), Kathmandu (1,400 m from sea level) and Lukla (2,860 m from sea level). The isolated organisms were characterized and tested for their susceptibility against different antibiotics. Results: Altogether 231 bacterial isolates were characterized from 166 skin samples. Among them, 140 isolates (60.60 %) were Gram positive and 91 isolates (39.40 %) were Gram negative bacteria. Staphylococcus aureus (35.49%) was the most dominant skin bacterial flora followed by Escherichia coli (22.51%) and Streptococcus spp. (17.75%). Medium altitude Kathmandu exhibited the highest growth (120 isolates) followed by low land Bharatpur (66 isolates) and high land Lukla (51 isolates) which is statistically significant (p value =0.0124). The antibiotic susceptibility testing against 14 antibiotics exhibited the Gram positive isolates were the most sensitive to Imipenem (94.93 %) whereas the least sensitive to Cephalexin (31.36 %) and the Gram negative isolates were the most sensitive to Amikacin (100%) whereas the least sensitive to Amoxycillin (28.57 %). Conclusion: Our data indicates that the skin bacterial normal flora; which is directly exposed to external environment; has significant relationship with altitudes where individuals live. The result desires further study for the adaptability of normal flora found in different altitudes. Some bacterial commensals were found resistant even against new generations of antibiotics as well, and hence can cause life-threatening infections if they happen to cross the skin physical barrier.